Nilai Sosial Budaya Cerita Rakyat Batu Plantolan Masyarakat Jereweh Kabupaten Sumbawa Barat dan Hubungannya dengan Pembelajaran Sastra - Ayu Triana Putri; Mahsun; Burhanuddin (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2022)
This study aims to analyze the text structure, language tools, and socio-cultural values ​​contained in the BatuPlantolan folklore of the Jereweh community, West Sumbawa Regency and describe the relationship between values socio-cultural story of the BatuPlantolan people of the Jereweh community by learning literature. The data collection in this study used the listening or note-taking method and the conversation or interview method. The results of this study indicate that the BatuPlantolan folklore has a narrative text structure (title, introduction/orientation, problems/complications, problem solving), using tools (repetition/repetition, anaphoric, connecting conjunctions between paragraphs), socio-cultural values ​​(please help, sense of belonging). love parents for their children, empathy). Based on the results of this study, it can be stated that the socio-cultural value of BatuPlantolan folklore has a relationship with literary learning.